Remote hearing screenings via telehealth in a rural elementary school. - Lancaster P; Krumm M; Ribera J; Klich R (American Journal of Audiology, 2008)
PURPOSE: Telehealth (telepractice) is the provision of health care services using telecommunications. Telehealth technology typically has been employed to increase the level of health care access for consumers living in rural communities. In this way, audiologists can use telehealth to provide services in the rural school systems. This is important because school hearing screening programs are the foundation of educational audiology programs. Therefore, the goal of this study was to determine the feasibility of providing hearing screening services by telehealth technology to school-age children. METHOD: Hearing screening services-including otoscopy, pure-tone, and immittance audiometry-were conducted on 32 children in 3rd grade attending an elementary school in rural Utah. Each child received 1 screening on-site and another through telehealth procedures. RESULTS: Immittance and otoscopy results were identical for on-site and telehealth screening protocols. Five children responded differently to pure-tone stimuli presented by the telehealth protocol than by the on-site protocol. However, no statistically significant difference was found for pure-tone screening results obtained by telehealth or on-site screening procedures (binomial test, p = .37). Likewise, overall screening results obtained by traditional and telehealth procedures were not statistically significant (binomial test, p = .37). CONCLUSION: The results of this study suggest that school hearing screenings may be provided using telehealth technology. This study did find that 5 students performed differently to pure-tone screenings administered by the telehealth protocol in contrast to on-site hearing screening services. Further research is necessary to identify factors leading to false responses to pure-tone hearing screening when telehealth technology is used. In addition, telehealth hearing screening protocols should be conducted with participants of different age groups and experiencing a wide range of hearing loss to further clarify the value of telehealth technology.